Ultrasensitive Detection of Neurotransmitter in Neurological Disorders - Kiran Kayani; Hijab Fatima; Fahad Bhopal; Jamshed Aftab; Naureen Ehsan Ilahi; Asma Gul; Dr Madeeha Chaudhry (NUST Journal of Engineering Sciences)
Psychological or neurological disorders have worldwide prevalence of 10-13 %. In Pakistan the situation is equally alarming affecting 10-16% of the population. Among all the neurological diseases the most prevalent one in Pakistani population are: depression (6%), schizophrenia (1.5%) and epilepsy (1-2%). Dopamine, a critical neurotransmitter plays an important role in onset and progression of aforementioned disorders. Normal dopamine levels in human blood are 0 to 30 pg/mL (195.8 pmol/L). A little variation in its levels can cause onset of depression and various neurological diseases. Conventional dopamine detection techniques are laborious and time consuming that’s why less commonly practiced in Pakistani clinics. We propose an immunoassay chip offering optical detection of different log dilutions (1/10, 1/100 and 1/1000) of dopamine using CdSe/ZnS quantum dots (QDs). Elucidation of fluorescence response of different dilutions of quantum dot conjugated dopamine antibody revealed maximum fluorescence intensity at 1/10 dilution. This demonstrates the efficiency and sensitivity of the current method. The current study would be revolutionary in proposing a timely diagnosis of dopamine levels to patients suffering from neurological problems. Similarly, facilitating timely diagnosis and personalized treatment for patients with neurological disorders.